Software engineering methods and management - Zelkowitz, Marvin V., 1945- (San Diego : Academic Press, 2001)
Volume 54 presents six chapters on the changing face of software engineering-the process by which we build reliable software systems. We are constantly building faster and less expensive processors, which allow us to use different processes to try and conquer the "bug" problem facing all developments-how to build reliable systems with few errors at low or at least manageable cost. The first three chapters of this volume emphasize components and the impact that object-oriented design is having on the program development process (a current "hot topic"). The final three chapters present additional aspects of the software development process, including maintenance, purchasing strategies, and secure outsourcing of scientific computations.
Includes bibliographical references and indexes.
Keywords: Software engineering; Electronic books